BAHAN AJAR ELEKTRONIK BERBASIS CAMTASIA UNTUK MENINGKATKAN HASIL BELAJAR MAHASISWA - Fachruddiansyah Muslim; Riyo Riyadi (Sosio-Didaktika: Social Science Education Journal, 2019)
AbstractThis study aims to produce electronic teaching materials in macroeconomic theory courses. The methodology of this research is the development of a 4D model that includes defining, designing, developing, and disseminating completed through questionnaires and tests. To obtain data in the form of assessments from experts regarding the product being developed as well as responses from students on the use of the product. Data analysis used presentation techniques from experts and student responses and the results of tests conducted during field trials. The results showed that first, the electronic teaching materials on the Camtasia-based Macroeconomic Theory course developed with the 4D model can produce interesting and effective teaching materials, secondly, the instructional materials developed have a positive effect on improving student learning outcomes. From the results of this study, it is suggested that any course material development in the lecture process can develop Camtasia-based electronic teaching materials because they are easily accessed and developed with other products.Keywords: Camtasia-Based Electronic Teaching Materials, and Learning Outcomes.                                                     AbstrakPenelitian ini bertujuan untuk menghasilkan bahan ajar elektronik pada mata kuliah teori makro ekonomi. Metodologi penelitian ini berupa pengembangan model 4D (4 Dimensi) yang mencakup pendefinisian (define), perancangan (design), pengembangan (develop), dan penyebaran (disseminate) yang dilengkapi melalui kuesioner dan tes. Dalam rangka memperoleh data berupa penilaian dari para ahli mengenai produk yang dikembangkan serta respon dari mahasiswa atas penggunaan produk tersebut. Analisis data menggunakan teknik presentase dari para ahli dan respon siswa serta hasil tes yang dilakukan pada saat uji coba lapangan. Hasil penelitian menunjukkan bahwa pertama, bahan ajar elektronik pada mata kuliah Teori Ekonomi Makro berbasis camtasia yang dikembangkan dengan model 4D tersebut dapat menghasilkan bahan ajar yang menarik dan efektif, kedua bahan ajar yang dikembangkan memiliki efek positif dalam meningkatkan hasil belajar mahasiswa. Dari hasil penelitian ini disarankan agar setiap pengembangan bahan mata kuliah dalam proses perkuliahan dapat mengembangkan bahan ajar berbasis elektronik berbasis camtasia karena mudah diakses dan dikembangkan dengan produk yang lain.Kata Kunci: Bahan Ajar Elektronik Berbasis Camtasia, dan Hasil Belajar.